1993
DOI: 10.1530/jrf.0.0990617
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive monitoring of ovarian function in Asian elephants (Elephas maximus) by measurement of urinary 5 -pregnanetriol

Abstract: The development of an enzymeimmunoassay for 5\g=b\-pregnanetriol and its use for non\x=req-\ invasive monitoring of reproductive cycles in Asian elephants is described. Gas chromatography\p=n-\massspectrometry (GCMS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Rather, the major circulating luteal progestins in Asian and African elephants are 5a-pregnane-3,20-dione (5aDHP) and 5a-pregnane-3-ol-20 one (5a-P-3-OH), with 5aDHP predominating Hodges et al, 1997;Schwarzenberger et al, 1997]. In the Asian elephant, 17a-hydroxyprogesterone (17a-OHP) is also present in the circulation, although it is not as abundant as 5aDHP [Niemuller et al, 1993;Hodges, 1998]. Despite the higher immunoactivity exhibited by CL425 in the EIA, the two serum profiles were qualitatively similar throughout the luteal phase and pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, the major circulating luteal progestins in Asian and African elephants are 5a-pregnane-3,20-dione (5aDHP) and 5a-pregnane-3-ol-20 one (5a-P-3-OH), with 5aDHP predominating Hodges et al, 1997;Schwarzenberger et al, 1997]. In the Asian elephant, 17a-hydroxyprogesterone (17a-OHP) is also present in the circulation, although it is not as abundant as 5aDHP [Niemuller et al, 1993;Hodges, 1998]. Despite the higher immunoactivity exhibited by CL425 in the EIA, the two serum profiles were qualitatively similar throughout the luteal phase and pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The urinary pattern produced by the EIA similarly mimicked circulating profiles, although the data were somewhat more variable. In Europe, urinary monitoring of reproductive status in the elephant typically is conducted by analyzing progestagen metabolites (5a-P-3OH in African Fiess et al, 1999] and pregnanetriol in Asian [Niemuller et al, 1993] …”
Section: Discussionmentioning
confidence: 99%
“…The previously established EIA methodologies for progesterone and its metabolites (P m ) in elephants were applied to determine hormone concentrations from serum [28] or urine [9]. The protocols for serum P m analysis were slightly adapted as previously published [27].…”
Section: (A) Elephantsmentioning
confidence: 99%
“…Since then, the anatomy of the reproductive tract with an 1.5 m long vestibulum (canalis urogenitalis) preceding the vagina [3,4], and ovaries showing multiple corpora lutea (CLs) [5][6][7][8], as well as the secretion of reproduction-associated hormones have been the focus of much research. Elephants show a double luteinizing hormone (LH)-peak during the follicular phase and a 12-16 weeks long oestrous cycle [9][10][11]. The pregnancy lasts from 620 to 680 days, which led to research interest on placentation and embryonic development [4,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The picture that has emerged indicates a wide range of endocrine patterns in wildlife species. For example, non-invasive monitoring has indicated that okapi have an estrous cycle length of only 2 weeks (Loskutoff et al, 1982;Schwarzenberger et al, 1999), killer whales have an estrous cycle length of 6 weeks (Walker, et al, 1988;Robeck et al, 1993) and elephants have an estrous cycle length of 13 to 16 weeks (Niemuller et al, 1993;Heistermann et al, 1997;Fiess et al, 1999). Fecal steroid analysis has indicated that felids are primarily induced ovulators although incidences of spontaneous ovulations have been observed (see reviews by Brown, 1997, andBrown et al, 2001).…”
Section: Applicationsmentioning
confidence: 99%